Role of Drug Remedies in Attention Deficit Hyperactivity Disorder (ADHD): A Case Series (Advancements in Homeopathic Research, 2024)
Introduction: ADHD is the most common neurobe havioral disorder in children which comprises of 3  types: inattentive/hyperactive-impulsive/combined  type. There are varied drugs in homoeopathy belong ing to narcotic groups which seems to be effective in  these type of cases. These groups have various alka loids whose main sphere of action is on CNS or PNS  as stimulant, depressor or hypnotic.  Case summary: Here, 3 cases are presented with  different types of ADHD as diagnosed by Vanderbilt  Diagnostic Scale. In all these cases homoeopathic  drug remedies were prescribed on the basis of  totality of symptoms. Marked improvement in all the  cases substantiate the effectiveness of homoeopathy  especially drug remedies in these type of behavioural  problems when given constitutionally.
Keywords: ADHD; homoeopathy; narcotics; drug remedies; Vanderbilt diagnostic scale